Предмет: Алгебра, автор: MasteRrRik

помогите, алгебра подготовка к ЕГЭ
 \sqrt[4]{(1 - 2x +  {x}^{2})( {x}^{2} - 1)(x - 1)  }  \times  \frac{ \sqrt[4]{x  + 1} }{ {x}^{2}  + 2x - 3}
при
 - 1 \leqslant x \leqslant 0

Ответы

Автор ответа: vahe2907
1

\sqrt[4]{(1-2x+x^2)(x^2-1)(x-1)} *\frac{\sqrt[4]{x+1}}{x^2+2x-3} = \sqrt[4]{(x-1)^4*(x+1)}*\frac{\sqrt[4]{x+1}}{x^2+2x-3} = (x-1)*\frac{\sqrt{x+1}}{x^2+2x-3} = (x-1)*\frac{\sqrt{x+1}}{(x-1)(x+3)} = \frac{\sqrt{x+1}}{x+3}\\x = -1; \frac{\sqrt{x+1}}{x+3} = 0;\\x = 0; \frac{\sqrt{x+1}}{x+3} = \frac13

[0; \frac13]

Похожие вопросы
Предмет: Математика, автор: aleksandra071228